The effects of phonics instruction on L2 phonological decoding and vocabulary learning: An experimental study of Chinese EFL learners. (December 2021) - Li, Sha; Woore, Robert
Abstract: Phonological decoding – defined here as the ability to convert the written forms of an alphabetic writing system into the phonological forms they represent, using knowledge of the language's symbol-sound correspondences (SSC) – may play an important role in various aspects of second language (L2) learning, including the crucial task of vocabulary learning. Yet, many L2 learners appear to have low phonological decoding proficiency, even after extensive exposure to the language. Phonics instruction – explicit teaching of a language's SSC – has been found to improve phonological decoding amongst first language (L1) beginner readers. However, there is limited evidence concerning the effects of phonics instruction in L2. Addressing this gap, we conducted a quasi-experimental study in which two classes of first-year English majors (n = 71) in two Chinese universities received twelve weeks of English phonics instruction. A comparison group comprising parallel classes in the same universities (n = 67) received twelve weeks of instruction in English phonology, but without phonics. Pre- and post-tests measured participants' phonological decoding and vocabulary memorisation; the latter was assessed by immediate recall tests and recognition tests of the new words' phonological and orthographic forms. The phonics group significantly outperformed the comparison group in both post-tests, with medium effect sizes.